MARKET ORIENTATION: COMPANY PERFORMANCE AND GLOBAL CONSUMER CULTURE CHANGE - Stanny S. Rawung (AIBPM Publisher, 2019)
Market orientation (market orientation) is a measure of behavior and activity that reflects the implementation of the marketing concept. Ironically, although the marketing concept has been developed in the decade of the 1950s, it was only in the 1990s that empirical studies began to be conducted to examine the marketing concepts of business strategy and success. In line with the development of the business world today a term